Cosmovisão nas práticas discursivas da nova direita: um estudo de caso da chapa Arthur do Val na campanha eleitoral de 2020 em São Paulo - Ferreira, Rodrigo da Silva (2023)
This dissertation aims to understand the discursive strategies of the Arthur do Val group — a political agent allied with the new right camp — employed during the political campaign for mayor of São Paulo in 2020. Devoid of a political-family history, the scenario promoter to enter a political space in dispute, include mobilizations through digital media and the large demon-strations that began in 2013 and ended with the impeachment of President Dilma Rousseff (PT). The question that guides this research is: how were the discursive strategies of the new young right, represented by the Arthur do Val ticket in the São Paulo elections in 2020, designed to compete for a political space consolidated by traditional political groups? From this perspective, the research centralizes as an object of analysis, primarily, the speeches given during the polit-ical campaign of the ticket between the period of August and November 2020 published through digital media (Youtube, Instagram, Telegram and Twitter) by Arthur do Val. In a second stage, it collects the speeches prepared during the launch period of the “Mamãe Falei” channel on YouTube, at the end of 2015. Starting from the methodological perspective of the theory of discourse proposed by Laclau and Mouffle, the strategies of the new right of Arthur do Val's campaign analyzed in this dissertation, starts with mapping the discursive construction and a reality proposed by the ticket, its worldview; and the ways in which a worldview passes through discursive practices, structure and form part of the strategies used in the group’s practical ac-tion. The collected data, treated and analyzed through Atlas TI and Gephi, allowed us to under-stand how the discursive-narrative forms of the panel are triggered through a performative set of media action, developing a supposed idea of understanding reality, mapping the actors and conditioning factor for the construction of a social fact. The speeches and discursive practices of Arthur do Val centralized the left as the opponent, developing the argument based on three premises: i) reduction of the State in the economy; ii) left as something bad; iii) the left articu-lated with mafias. The research shows that the discursive strategies used disputed, based on experiencing and promoting the discursive construction of a fact, the category of truth on a topic in dispute. These strategies, organized in a process of discursive triggering, elaborate the notion of truth by locating the effects, the causing reasons and the actors involved; used as a way of guiding the understanding of those who accompany it and developing a solution to a social problem.